1996
DOI: 10.1300/j091v04n01_08
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization Response on Growth, Photosynthesis, Starch Accumulation, and Leaf Nitrogen Status ofCassia siameaLam. Seedlings Under Nursery Conditions

Abstract: Nitrogen, phosphorus, and potash fertilizers in eight treatment combinations. inchdine. an unfertilized control treatment were given to Cassia siamea seedlings under nursery conditions. This study was carried out to identify the physiological basis of varying growth response due to fertilization. Nitrogenous fertilizer application increased seedling growth, whereas application of phosphorus or potash fertilizers, either separately or in conjunction, did not improve seedling growth. Starch level had increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The lack of phenolic responses by yaupon to nitrogen addition indicates the need for alternatives to the mechanism set forth by the CNB hypothesis for interpretation of these results. Although the CNB hypothesis predicts that carbon allocation to carbon-based secondary metabolism decreases with nitrogen fertilization due to faster rates of growth relative to photosynthesis (Bryant et al 1983), nitrogen fertilization does not necessarily favor growth over photosynthesis (Kannan and Paliwal 1997). Furthermore, even when nitrogen additions stimulate biomass accumulation but not photosynthetic rates, phenolic concentrations do not always decrease (Reichardt et al 1991;Bezemer et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of phenolic responses by yaupon to nitrogen addition indicates the need for alternatives to the mechanism set forth by the CNB hypothesis for interpretation of these results. Although the CNB hypothesis predicts that carbon allocation to carbon-based secondary metabolism decreases with nitrogen fertilization due to faster rates of growth relative to photosynthesis (Bryant et al 1983), nitrogen fertilization does not necessarily favor growth over photosynthesis (Kannan and Paliwal 1997). Furthermore, even when nitrogen additions stimulate biomass accumulation but not photosynthetic rates, phenolic concentrations do not always decrease (Reichardt et al 1991;Bezemer et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the topsoil analysis (Table 7) It is unsure that by supplying inorganic nutrients to media or substrates through fertilizer, they will be useful for the wildling growth. Kannan & Paliwal (2008) had studied about the effects of nitrogen, phosphorus, and potash fertilizers on Cassia siamea seedlings under nursery conditions. Kannan & Paliwal (2008) concluded that the effects of nitrogen increased seedling growth, whereas phosphorus or potash fertilizers, either separately or in combination, did not improve seedling growth.…”
Section: Discussionmentioning
confidence: 99%
“…Kannan & Paliwal (2008) had studied about the effects of nitrogen, phosphorus, and potash fertilizers on Cassia siamea seedlings under nursery conditions. Kannan & Paliwal (2008) concluded that the effects of nitrogen increased seedling growth, whereas phosphorus or potash fertilizers, either separately or in combination, did not improve seedling growth. It was concluded that natural chemical properties of soil are very important factors supporting the wildling growth, and therefore findings in the present research showing that the topsoil located close to the base of mother trees is very useful in cultivating trees, especially when utilizing topsoil from the forests as growth media.…”
Section: Discussionmentioning
confidence: 99%